From The Real Word To Cyber World - Robyan Bafadal (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
One of the problems an organization faces when its founder dies. Many factions then fought over the position. It even involves the descendants of its founder. So there are often clashes between the competing parties. Clashes can be in the form of hate speech or physical clashes. In today's era of social media, his role is like a double-edged knife. Can reconcile or cause conflict to deepen. Social media can reconcile with the condition that the upload is in the form of sentences that soothe the parties experiencing the conflict. In our research, we found that social media can then quell conflict, at least move conflict from the real world to the virtual world